The Study of Diversity and Intensity of Pest Attacks on Arabica Coffee (Coffea arabica l.) Plantations in Kutarayat Village, Naman Teran District, Karo Regency - Nur Ikhsan; Kabul Warsito; Andi Setiawan (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
The high demand for Arabica coffee (Coffea arabica [A1] L.) in North Sumatra must be accompanied by high productivity as well. One of the challenges often faced by coffee farmers is pest attacks. One way to address this issue is by conducting surveys on pest diversity and the intensity of pest attacks on coffee plantations. This study is a descriptive quantitative analysis with a cluster sampling method (sampling area) using yellow traps. The observation area covers 5 hectares, spread across 5 hamlets. Each hamlet consists of 5 plots, with each plot covering an area of 250 m². The observation period was divided into 4 sessions: morning, afternoon, evening, and night. The results of the observations showed that in Block 1, the total number of Diptera order was 105 individuals with a KR value of 77.5%, and the lowest order was Orthoptera with only 1 individual and a KR value of 3%. In Block 2, the order Diptera had 103 individuals with a KR value of 79.75%, and the lowest order was Odonata with 1 individual and a KR value of 2%. In Block 3, the most frequent order was Diptera with 57 individuals and a KR value of 68%, while the lowest order was Neuroptera with 1 individual and a KR value of 3%. In Block 4, the most frequent order was Hymenoptera with 59 individuals and a KR value of 39.5%, and the lowest order was Neuroptera with 1 individual and a KR value of 3%. In Block 5, the most frequent order was Diptera with a total of 60 individuals and a KR value of 65.5%, while the lowest order was Coleoptera with 1 individual and a KR value of 5%